2008
DOI: 10.1210/jc.2008-1104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Selective Progesterone Receptor Modulator Asoprisnil on Uterine Artery Blood Flow, Ovarian Activity, and Clinical Symptoms in Patients with Uterine Leiomyomata Scheduled for Hysterectomy

Abstract: Asoprisnil moderately reduced uterine artery blood flow. This effect may contribute in part to the clinical effects of asoprisnil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 35 publications
3
77
0
1
Order By: Relevance
“…5, 10 ve 25 mg/gün dozlarında sırasıyla kanama miktarını %28, %64 ve %83 oranında azaltmaktadır (40). Ayrıca 25 mg dozunda leiomyom volümünde %36 küçülme izlenmektedir (41). Yalnızca progesteron antagonisti olarak etki etmekte ve endometriumda östrojen aktivitesini inhibe etmemektedir (42).…”
Section: Selektif Progesteron Reseptör Modülatörleriunclassified
“…5, 10 ve 25 mg/gün dozlarında sırasıyla kanama miktarını %28, %64 ve %83 oranında azaltmaktadır (40). Ayrıca 25 mg dozunda leiomyom volümünde %36 küçülme izlenmektedir (41). Yalnızca progesteron antagonisti olarak etki etmekte ve endometriumda östrojen aktivitesini inhibe etmemektedir (42).…”
Section: Selektif Progesteron Reseptör Modülatörleriunclassified
“…Compared with progesterone, asoprisnil has a high tissue selectivity and higher binding affinity to progesterone receptors [53]. It induces amenorrhea and reduces uterine fibroid volume in a dose-dependent manner [54,55], and it reduces uterine artery blood flow [56]. Asoprisnil has marginal abortifacient activity and no antiglucocorticoid effect [57][58][59][60].…”
Section: Selective Progesterone Receptor Modulatorsmentioning
confidence: 99%
“…Given the anti-proliferative effects observed in vitro and in vivo for PRAs (Freeburg et al, 2009b;Goyeneche et al, 2007;Ohara et al, 2007;Poole et al, 2006;Tieszen et al, 2011), the broader utility of this class in treating other benign and malignant growth conditions has not gone unnoticed Robertson et al, 1999;Rocereto et al, 2000;Wilkens et al, 2008). In the closely related condition of uterine fibroids, small studies have demonstrated a reduction in myoma volume and uterine bleeding with asoprisnil and RU-486 (Chabbert-Buffet et al, 2005;DeManno et al, 2003;Fiscella et al, 2006).…”
Section: Clinical Evaluation In Healthy Women and Women With Endometrmentioning
confidence: 99%